Pengaruh Faktor Internal dan Eksternal terhadap Minat Gapoktan Jarak Kulon Kabupaten Jombang dalam Pemanfaatan POC Limbat (The Influence of Internal and External Factors on the Interest of the Jarak Kulon Farmers Group, Jombang Regency in Utilizing POC Limbat) - Wardany, Mochammad Rheza Randi; Despita, Rika; Romadi, Ugik (Jurnal Ilmiah Sosio Agribis, 2025)
The long-term use of chemical fertilizers in agricultural practices can reduce the quality of soil and the environment. One of the alternatives to a more environmentally friendly sustainable solution is the use of tofu liquid waste as liquid organic fertilizer (POC Limbat). This study aims to analyze the interest of farmers of Gapoktan Jarak Kulon, Jogoroto District, Jombang Regency in adopting POC Limbat, which is influenced by internal and external factors. The internal factors analyzed included age, education level, and participation in the group, while external factors included the availability of resources and the intensity of counseling, using quantitative methods based on multiple linear regression analysis. In the results of the study, it was shown that internal factors did not have a significant effect on farmers' interests, while the availability of resources and the intensity of extension were proven to have a significant positive influence. The contribution of increasing interest from the resource factor reached 0.931%, while from extension reached 0.813%, so that it can encourage the adoption of agricultural innovations that are more environmentally friendly, especially in the use of local waste.Keywords: Tofu Waste, POC, Farmer Interest, Internal Factors, External Factors